Hábitos alimentares e cultura local: desvelando discursos e marcas identitárias em Belo Jardim-PE - Marangon., Adalva Cordeiro Galvão (2009)
This study discusses about food practice speeches of cook women in Belo Jardim, Pernambuco, in rural and urban zone, analyzing, in voices of these women, the meanings produced in the discursive practice of orality, their stories, the identity marks of the city through food practices. The research material is, in essence, interviews on the making of these women, as well as information from other people of the community. It examines aspects relating to historical memory, revived by the subjects in this city and their daily, the spaces of silence in the voices of the interviewees, as well as crossed cultural aspects and/or directly connected to what is conservative and innovative in doing and/or the resistance to new, to the new technology and its use in kitchens. Get records of historical heritage of food, emphasizing its importance in society and in academic circles, which promotes a better dialogue multi, inter and transdisciplinary. It shows, through the cultural history, the gastronomic sensitivity, and its social dynamic, explained by social and cultural events: the eating like a social act constitutes attitudes linked to the habits and customs, behaviors and situations. It also discourses about issues such as the identity crisis, occurred with the structural change in modern societies in compliance with food practices on women's voices cooks. Inventions and reinventions in daily women in times of crisis and abundance. Theoretical and methodological basics that guide the search is based on studies examining of Discourse Analysis of french guidance, particularly Michel Pêcheux, Michel Foucault and also Eni Orlandi. Other sources support this study, like Eclea Bosi on the interrelations between memory and society, Jacques Le Goff, Michel de Certeau, Louis da Câmara Cascudo, Jean-Louis Flandrin, Roberto DaMatta, José Carlos Sebe Bom Meihy. It is noted by this research that the oral narratives say much about the history of everyday life, cultural practices and identities of a place, recalled for ideological discourses, translated in the construction of the senses. Keywords: Discourse Analysis. Feeding practices. Culture. Identity.